Protozoan and Helminth Infections of Aviary-Reared Alectoris rufa (Galliformes: Phasianidae) before Releasing for Hunting in the Czech Republic: Infection Dynamics and Potential Risks - Máca, O; Pavlásek, I (The Journal of parasitology, 2020)
Age-related dynamics of protozoan and helminth infections in the red-legged partridge, Alectoris rufa, were studied in an intensive breeding aviary in the Czech Republic before releasing birds for hunting purposes. Pooled fecal samples (n = 900) were examined over 3 rearing seasons (2012-2014). A total of 4 protozoan species, Cryptosporidium baileyi, Cryptosporidium meleagridis, Eimeria kofoidi, and Eimeria legionensis, and 4 helminths, Capillaria phasianina, Eucoleus perforans, Heterakis gallinarum, and Syngamus trachea, was found. The most common parasite was S. trachea (prevalence 20-26%) in dead birds (n = 99), which represents a high risk for breeders. Co-occurrence of protozoans and helminths indicated similarities in infection dynamics throughout the 3 breeding seasons. Mixed infections of Cryptosporidium baileyi and C. meleagridis with other parasitic species are reported for the first time. Our findings provide new insights into breeding of A. rufa and may help to improve the efficacy of disease control strategies and prevention, especially with the potential for spreading of parasitic infections to wildlife through released birds into open areas.
Keywords: Infection Dynamics; Syngamus; Zoonotic Potential; feces; Helminthiasis, Animal; Birds; Alectoris rufa; helmintózy zvířat; prevalence; nemoci ptáků; Nematoda; rizikové faktory; věkové faktory; Capillaria; Cryptosporidium; Spirurida; zvířata; Red-Legged Partridge; Protozoan Infections, Animal; Galliformes; Eimeria; cizopasní červi; Feces; hlístice; Helminths; Czech Republic; Prevalence; Age Factors; Animals; Strongyloidea; Bird Diseases; Česká republika; Heterakis; protozoální infekce zvířat; Eucoleus; Risk Factors